Effects of an exercise intervention based on the COM-B model among community-dwelling prefrail older adults with diabetes: study protocol for a randomised controlled trial - Yang Zhao; Lu Chen; Ting-Ting Wang; Jun Yang; Ju Qiu; Wen-Xin Wang; Ling-Na Kong (BMJ Open)
Introduction Prefrailty is common among community-dwelling older adults with diabetes and can lead to adverse health outcomes. With effective exercise interventions, prefrailty is reversible. However, there is a paucity of evidence regarding the effects of exercise interventions for prefrail older adults with diabetes. This study presents a study protocol for evaluating the effectiveness of an exercise intervention based on the Capacity, Opportunity and Motivation Behaviour (COM-B) model among community-dwelling prefrail older adults with diabetes.Methods and analysis Using a randomised controlled trial design, a total of 100 community-dwelling prefrail older adults with diabetes will be allocated to either an intervention or a control group in a 1:1 ratio. Participants in the intervention group will receive a 16-week multicomponent exercise intervention based on the COM-B model, while those in the control group will receive usual diabetes care and general advice on physical activity. The primary outcome is frailty status, and the secondary outcomes include physical function, quality of life, depressive symptoms, self-efficacy for exercise and fasting blood glucose. Assessments will be conducted at baseline, week 8 and week 16.Ethics and dissemination This study has been approved by the Ethics Committee of the First Affiliated Hospital of Chongqing Medical University (approval number: K2023-320). The findings will be submitted to a peer-reviewed journal for publication.Trial registration number ChiCTR2400082831.